Clinical Outcomes of Methotrexate Usage in Postoperative Arthroplasty Patients: An Evidence Based Review - Koppert J; Heikoop D; Lanting BA (Orthopedic Research and Reviews, 2025)
Jason Koppert, David Heikoop, Brent A Lanting Department of Orthopaedic Surgery, Schulich School of Medicine, Western University, London Health Sciences Center, London, Ontario, CanadaCorrespondence: Brent A Lanting, London Health Sciences Center, 339 Windermere Road, London, ON, N6A 5A5, Canada, Tel +15196833335, Email brent.lanting@lhsc.on.caAbstract: Patient dissatisfaction after joint arthroplasty remains common. Synovitis is known to contribute to patient dissatisfaction in patients with osteoarthritis. Methotrexate (MTX) is commonly used to prevent joint deterioration in rheumatoid arthritis, however it is much less common in the treatment of osteoarthritic patients. This review explores the effect of MTX on surgical outcomes in the general arthroplasty patient population. While most of the papers reviewed include patients with rheumatoid arthritis, we also review papers that include patients with osteoarthritis and juvenile idiopathic arthritis. Publications were queried in PUBMED and OVID MEDLINE using the following terms: arthroplasty, joint replacement, methotrexate, DMARDs, osteoarthritis, rheumatoid arthritis, arthritis. After applying exclusion criteria, we identified 12 publications for this review. Our results showed no significant increase in revisions or long-term infections were reported in patients taking MTX. One study reported detriment to nerve function with postoperative MTX use. All other studies reported no difference in post-operative pain or function scores. One study investigating the effect of MTX on mobility in rheumatoid arthritis patients following arthroplasty showed improvement in function in patients taking MTX. Thus, based on this review, perioperative MTX use does not appear to worsen arthroplasty outcomes. This review should suffice as a building block for further investigations and trials into MTX’s utility for arthroplasty patients.Keywords: DMARD, osteoarthritis, rheumatoid arthritis, arthritis, joint replacement